2014
DOI: 10.1371/journal.pone.0086806
|View full text |Cite
|
Sign up to set email alerts
|

Transport Rankings of Non-Steroidal Antiinflammatory Drugs across Blood-Brain Barrier In Vitro Models

Abstract: The aim of this work was to conduct a comprehensive study about the transport properties of NSAIDs across the blood-brain barrier (BBB) in vitro. Transport studies with celecoxib, diclofenac, ibuprofen, meloxicam, piroxicam and tenoxicam were accomplished across Transwell models based on cell line PBMEC/C1-2, ECV304 or primary rat brain endothelial cells. Single as well as group substance studies were carried out. In group studies substance group compositions, transport medium and serum content were varied, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 48 publications
(52 reference statements)
3
50
0
2
Order By: Relevance
“…Moreover, transport of caffeine was significantly further decreased in the quadruple culture compared with the mono-culture, indicating an even more in vivo-like phenotype in the quadruple culture. In concordance with in vitro data obtained from BBB models based on rat primary cells, ibuprofen was also faster than diclofenac in our models (Novakova et al., 2014). Loratadine and rhodamine 123 are known to be strong substrates of the efflux pump P-glycoprotein and to permeate significantly slower than diazepam (Obradovic et al., 2007, Neuhaus et al., 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, transport of caffeine was significantly further decreased in the quadruple culture compared with the mono-culture, indicating an even more in vivo-like phenotype in the quadruple culture. In concordance with in vitro data obtained from BBB models based on rat primary cells, ibuprofen was also faster than diclofenac in our models (Novakova et al., 2014). Loratadine and rhodamine 123 are known to be strong substrates of the efflux pump P-glycoprotein and to permeate significantly slower than diazepam (Obradovic et al., 2007, Neuhaus et al., 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that NSAIDs modulate expression of the ABC transporters [30][31][32][33][34][35] and possibly functions as substrates [30]. The present study supports these findings and suggests that carriers of polymorphisms that are associated with lower ABC transport activity benefit from the anti-inflammatory effect of the NSAIDs.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously found interaction between two polymorphisms in ABCB1 and red meat intake in relation to risk of CRC [29] which could be caused by a change in binding affinity or transport activity for PAHs and HCAs. Moreover, we found interaction between use of non-steroidal antiinflammatory drugs (NSAID) and an ABCB1 polymorphism which is in line with studies showing that several NSAIDs modulate expression of ABC transporters [30][31][32][33][34][35] or function as substrates for the ABC transporters [30]. In another study using the same study group as the present, we found interaction between several dietary factors and polymorphisms in genes encoding the cytokines interleukin 1-b (IL-1b) and IL-10 in relation to CRC risk [36].…”
Section: Introductionsupporting
confidence: 87%
“…Ibuprofen, like several NSAIDs, is metabolized by CYP2C9, as well as CYP2C19. NSAIDs have a high liposolubility, and studies have shown that they easily cross the BBB . No information is available regarding their transport at the BBB, even if the role of multidrug resistance‐associated protein 1, organic anion transporter, and P‐gp is suggested …”
Section: Nonsteroidal Anti‐inflammatory Drugsmentioning
confidence: 99%
“…49 No information is available regarding their transport at the BBB, 50 even if the role of multidrug resistance-associated protein 1, organic anion transporter, and P-gp is suggested. 49 The incidence of ADRs associated with ibuprofen in children is low. 51,52 Rare but potentially severe ADRs in children are upper gastrointestinal complications and kidney injury ( Table 3).…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%